A3.1 Pathogenic role of IL-17 producing double negative (DN) T cells in primary sjögren's syndrome. (31st January 2014) - Alunno, Alessia; Carubbi, Francesco; Bistoni, Onelia; Caterbi, Sara; Bartoloni, Elena; Santoboni, Gianluca; Mirabelli, Giulia; Cannarile, Francesca; Valentini, Valentina; Cipriani, Paola; Giacomelli, Roberto; Gerli, Roberto
Abstract : Background and Objectives: We recently demonstrated that a CD3 + T cell population, that lacks both CD4 and CD8 molecules, defined as double negative (DN), is expanded in the peripheral blood of patients with long-standing primary Sjögren's syndrome (pSS), produces IL-17, accumulates in minor salivary glands (MSGs) and is resistant to corticosteroids (CS) in vitro . Since IL-17 represents a key cytokine in the pathogenesis of pSS, we aimed to investigate glandular and peripheral DN T cells in early phases of the disease in order to verify a possible correlation with clinical parameters, MSGs histological patterns and possibly ectopic lymphoneogenesis. Materials and Methods: Paired samples of peripheral blood mononuclear cells and MSGs from early pSS patients were evaluated by flow cytometry and immunofluorescence staining respectively to quantify DN T cells. Histological analysis to assess histological scores, B/T cell segregation and the presence of germinal center-like structures (GCs) was also performed. Ten patients with long-standing disease and 15 normal controls (NC) were also enrolled. Disease activity was assessed by the EULAR Sjögren's syndrome disease activity index (ESSDAI) and patient reported dryness, fatigue, pain and global disease activity were recorded on a 100 millimeters (mm) visual analogic scale (VAS). Unstimulated salivary flow was also collected. Results: In early stages of pSS, circulating DN T cells appeared not to be expanded as it occurs in patients with long-standing disease and were inversely correlated to circulating CD4 + Th17 cells. The number of infiltrating DN T cells was associated with the extent of glandular involvement, defined with Tarpley biopsy score, and with the presence of GCs. Furthermore, dryness symptoms were directly correlated with glandular DN T cells and inversely correlated with circulating DN T cells. Circulating DN T cells displayed an in vivo activated phenotype, confirmed by the expression of CD25, CD69 and HLA-DR, which was not affected by the addition of CS to the culture, as it occurred for IL-17 expression. Conclusions: Our findings suggest that DN T cells are in vivo activated Th17 cells involved in the pathogenic mechanisms leading to glandular dysfunction and damage in pSS. Furthermore, DN T cells may play a role in ectopic lymphoneogenesis development occurring during the disease.